Development of Rubber Tire Gantry Crane (Prototype) Obstacles Avoidance Method Using a Single Sensor on Microcontroller Based - Md Sani, Zamani (2011)
Abstract - RTG crane is used to stack containers at the wharf. Because the size of the crane is too large and the operated at high place, it is nearly impossible for the operator to monitor the area under the crane. Currently, a pointing sensor system is installed but the crane still fails to stop if the obstacle is inside of the track due to low coverage of the pointing sensor system. In this paper, a new method is developed on a prototype system of RTG, to improve the current obstacle avoidance. The system is using servo motor to rotate an infrared sensor in order to cover the total area in the track. The results of new method is compared with the pointing sensor system and shown that the develop system has better performance from the pointing sensor system by increasing the sensing area to three point or almost all the track area by rotating the infrared sensor